2001
DOI: 10.1097/00005373-200108000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Blood Exacerbates the Remote Inflammatory Response to Murine Peritonitis

Abstract: Although blood alone in the peritoneal cavity was well tolerated, in conjunction with inflammation, it was synergistic in amplifying the systemic inflammatory response. The amplified lung injury in this model was associated with significant increases in circulating and lung tissue chemokine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Although various mediators other than these chemokines are known to be chemoattractants for neutrophils, investigation involving CXCR2 KO mice suggested that the neutrophil infiltration was regulated mainly through the CXCR2 protein in some cases, such as parasitic infection, bacterial infection, and wound healing (38 -42). Under inflammatory conditions, KC seems to play a major role in neutrophil infiltration and MIP-2 seems to act in concert with KC even if MIP-2 production is up-regulated (43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Although the affinity of MIP-2 toward CXCR2 is stronger than that of KC (16), there have been few reports suggesting that MIP-2 is a main player in an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Although various mediators other than these chemokines are known to be chemoattractants for neutrophils, investigation involving CXCR2 KO mice suggested that the neutrophil infiltration was regulated mainly through the CXCR2 protein in some cases, such as parasitic infection, bacterial infection, and wound healing (38 -42). Under inflammatory conditions, KC seems to play a major role in neutrophil infiltration and MIP-2 seems to act in concert with KC even if MIP-2 production is up-regulated (43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Although the affinity of MIP-2 toward CXCR2 is stronger than that of KC (16), there have been few reports suggesting that MIP-2 is a main player in an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…As bactérias e/ou endotoxina são as grandes responsáveis pelas alterações observadas nesse órgão, como o acúmulo de neutrófilos e edema, mediados pela IL-8 que induzem a migração dessas células inflamatórias. Achados patológicos que identificam tais alterações são: extenso edema intersticial, congestão capilar e células inflamatórias no pulmão 12,14,21 . Na avaliação histológica, a correlação entre o grau de comprometimento pulmonar através da contagem de neutrófilos por campo e o estado metabólico no rato induzido a sepse por peritonite fecal confirma a existência de resposta inflamatória sistêmica visto que no pulmão saudável não há neutrófilos nos septos pulmonares.…”
Section: Discussionunclassified
“…However, both of these studies only examined the effects in the first 24 hours after zymosan injection and did not examine the systemic response of MCP-1 to this peritoneal insult. Johnson et al [23] demonstrated that lung tissue MCP-1 correlated with lung injury score, and these studies were carried out over a course of 2 weeks, demonstrating an excellent human clinical MODS model. However, no mention of systemic MCP-1 is made.…”
Section: Discussionmentioning
confidence: 99%